Application of modeling service to improve student discipline of SMK kesehatan PGRI Magetan - Muhammad Sahril (Ikatan Bimbingan dan Konseling Sekolah)
An increasingly evolving world of education demands students to be intelligent and courteous. In order to form students who are smart and polite require good education. Modeling services are good exemplary services ranging from the most basic things that school counselors provide to learners. In this study the authors used descriptive qualitative research and using the type of phenomenological research. The data obtained from observation, interview, and documentation. The results showed that modeling services give a dominant impact in learning morals students. In the modeling learning done by the schools through the teaching staff are done in different ways by modeling the participants, and facilitating their students in doing this service. Modeling service is very influential for the development of student behavior, proven students experience a very significant change. Various characters of students who come from various circles, can be changed through the modeling services done school. In addition, the influence of counselor characteristics in modeling is also very influential in the success of service modeling. It can be concluded that modeling services by schools through well-characterized teaching staff can have a positive impact on their students. Can be proved from the progress of students who experience a gradual change in attitude.